Analysis of Prime Rice Seed Sales Volume in PT. Pertani (Persero) Semarang, Central Java - Alisyah, Rafifa; Handayani, Migie; Mukson, Mukson (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
This research aimed to perceive the trend of sales volume and to analyze the correlation of sale’s factors with prime rice seed sales volume in PT. Pertani (Persero) Semarang in 2016-2020. This research was conducted at PT. Pertani (Persero) Semarang, Central Java. The locus of this research was chose using purposive sampling method. This research used case study as a research method where researcher did the research intensively, deeply, and detailed about the sales of prime rice seed in PT. Pertani (Persero) Semarang. Primary data was collected from an interview with PT. Pertani (Persero) Semarang’s employees. Secondary data including monthly production report, monthly sales report, marketing report of prime rice seed product at PT. Pertani (Persero) Semarang was collected through a time series method for 5 consecutive years from 2016-2020. Data was analized with trend analysis and pearson correlation method. The result of trend analysis shows a positive trend of prime rice seed sales volume in 2016-2020. The result of pearson correlation analysis shows that prices and marketing expenses are strongly correlated.